PENGARUH PERBEDAAN INDIVIDUAL DAN KARAKTERISTIK SISTEM TERHADAP PENERIMAAN PENGGUNAAN TEKNOLOGI INFORMASI: REPLIKASI MODEL DI BIDANG E-JOB VACANCIES - Petra Surya Mega Wijaya; Fahmy Radhi (Faculty of Economics and Business, Universitas Gadjah Mada, 2004)
The objective of this study is to test the correlation between perceived ease-of-use variable and perceived usefulness variable, beliefs (perceived ease-of-use and perceived usefulness) against behavior intention to use. The study also test the relationship between individual differences (computer self efficacy and knowledge of search domain) and system characteristics, which consist of relevance, terminology, and screen design against belief variables. The study replicates Technology Acceptance Model (TAM) developed by Hong et al. (2002) and implements in e-job vacancy area. The study used 163 respondents that consist of two different undergraduate students, the faculty of economics and informatics students. The results show that there are significant correlations among the perceived ease-of- use variable and perceived usefulness against behavior intention to use, computer self- efficacy and perceived ease-of-use variable, relevance and terminology variable against perceived usefulness. Surprisingly, there are no significant correlations between perceived ease-of-use and perceived usefulness variable. There are weak correlations between knowledge of search domain and relevance variable against perceived ease-of use variable, terminology against perceived usefulness, and screen design variable against perceived ease-of–use and perceived usefulness.